Si-Wu-Tang alleviates metabolic dysfunction-associated fatty liver disease by inhibiting ACSL4-mediated arachidonic acid metabolism and ferroptosis in MCD diet-fed mice - Xiaoyong Xue; Le Wang; Ruiyu Wu; Yufei Li; Runping Liu; Zhi Ma; Kexin Jia; Yinhao Zhang; Xiaojiaoyang Li (BMC, 2024)
Abstract Background Metabolic dysfunction-associated fatty liver disease (MAFLD) is a prevalent chronic liver disease worldwide. Si-Wu-Tang (SWT), a traditional Chinese medicine decoction has shown therapeutic effects on various liver diseases. However, the hepatoprotective effects and underlying mechanism of SWT on MAFLD remain unclear. Methods First, a methionine-choline-deficient (MCD) diet-fed mice model was used and lipidomic analysis and transcriptomic analysis were performed. The contents of total iron ions, ferrous ions, and lipid peroxidation were detected and Prussian blue staining was performed to confirm the protective effects of SWT against ferroptosis. Finally, chemical characterization and network pharmacological analysis were employed to identify the potential active ingredients. Results Serological and hepatic histopathological findings indicated SWT's discernible therapeutic impact on MCD diet-induced MAFLD. Lipidomic analysis revealed that SWT improved intrahepatic lipid accumulation by inhibiting TG synthesis and promoting TG transport. Transcriptomic analysis suggested that SWT ameliorated abnormal FA metabolism by inhibiting FA synthesis and promoting FA β-oxidation. Then, ferroptosis phenotype experiments revealed that SWT could effectively impede hepatocyte ferroptosis, which was induced by long-chain acyl-CoA synthetase 4 (ACSL4)-mediated esterification of arachidonic acid (AA). Finally, chemical characterization and network pharmacological analysis identified that paeoniflorin and other active ingredients might be responsible for the regulative effects against ferroptosis and MAFLD. Conclusion In conclusion, our study revealed the intricate mechanism through which SWT improved MCD diet-induced MAFLD by targeting FA metabolism and ferroptosis in hepatocytes, thus offering a novel therapeutic approach for the treatment of MAFLD and its complications. Graphical Abstract